Ubiquitous RFID network for highway monitoring and management - Johari, Jaiz A. Y; Al-Khateeb, Khalid A. Saeed (2006)
A simplified approach for the implementation of ubiquitous RFID networks in a Highway Management System is presented. The technique aims at deploying tagging identification in transport statistical analysis. The RFID network architecture has been designed as part of an existing system to make it more cost effective with a higher reliability. The usefulness and the merits of this easy access and user friendly approach are identified and discussed.